Using Extract From the Stems and Leaves of Yizhi (Alpiniae oxyphyllae) as Feed Additive Increases Meat Quality and Intestinal Health in Ducks - Ji, Fengjie; Gu, Lihong; Rong, Guang; Hu, Chengjun; Sun, Weiping; Wang, Dingfa; Peng, Weiqi; Lin, Dajie; Liu, Quanwei; Wu, Hongzhi; Dai, Haofu; Zhou, Hanlin; et al. (Frontiers in Veterinary Science, 2022)
Yizhi (Alpiniae Oxyphyllae, A. oxyphylla) has been widely used as an important traditional Chinese medicinal herb for centuries. Existing studies showed that A. oxyphylla has numerous benefits in human and animal health. We hypothesized that extract from the stems and leaves of A. oxyphylla (AOE) as feed additive may have positive effects on animal health and products. Thus, this study was conducted to evaluate the effects of AOE as feed additive on growth performance, serum biochemical parameter, intestinal morphology, microbial composition and meat quality in Jiaji ducks. A total of 240 Jiaji ducks of 42-day-old (1675.8± 44.2 g, male: female ratio = 1:1) were blocked based on body weight and randomly allocated into 4 treatments with 3 replicates that each had 20 duck individuals. The dietary treatments included: basal diet, control group (CK); basal diet supplementation with 30 mg/kg (Y1), 80 mg/kg (Y2), and 130 mg/kg (Y3) AOE, respectively, and lasted for 49 days. The results showed that average daily feed intake from day 42 to 60 was decreased with the increasing level of AOE (P < 0.05). Compared with CK group, The groups with AOE supplementation decreased serum LDL-C level (P < 0.05), the addition of 30 mg/kg AOE increased total amino acids, essential amino acids, branched-chain amino acids, nonessential amino acids, and umami taste amino acids in breast muscle (P < 0.05), whereas decreased selenium and zinc concentrations (P < 0.05). In addition, the supplementation of 30 or 130 mg/kg AOE significantly increased jejunal villus height (P < 0.05) and tended to increase the ratio of villus height to crypt depth in jejunum (P = 0.092) compared to CK group. Moreover, the addition of 30 mg/kg AOE showed higher abundance of genus unclassified Bacteroidales and genus unclassified Ruminococcaceae than CK group (P < 0.05). Therefore, dietary supplementation with 30 mg/kg AOE increased meat nutrition profile and flavor through promoting amino acid contents in breast muscle, as well as maintained intestine integrity, and modulated the microbialmicrobiota composition. In conclusion, AOE as antibiotic alternative displayed the potential in maintaining intestinal health and improving meat quality.